Fundamentals of game design. - Adams, Ernest, ....- (Berkeley : New Riders, 2010)
To create a great video game, you must start with a solid game design: A well-designed game is easier to build, more entertaining, and has a better chance of succeeding in the marketplace. Here to teach you the essential skills of player-centric game design is one of the industry's leading authorities, who offers a first-hand look into the process, from initial concept to final tuning. Now in its second edition, this updated classic reference by Ernest Adams offers a complete and practical approach to game design, and includes material on concept development, gameplay design, core mechanics, user interfaces, storytelling, and balancing. In an easy-to-follow approach, Adams analyzes the specific design challenges of all the major game genres and shows you how to apply the principles of game design to each one. You'll learn how to: Define the challenges and actions at the heart of the gameplay. Write a high-concept document, a treatment, and a full design script. Understand the essentials of user interface design and how to define a game's look and feel. Design for a variety of input mechanisms, including the Wii controller and multi-touch iPhone. Construct a game's core mechanics and flow of resources (money, points, ammunition, and more). Develop appealing stories, game characters, and worlds that players will want to visit, including persistent worlds. Work on design problems with engaging end-of-chapter exercises, design worksheets, and case studies. Make your game accessible to broader audiences such as children, adult women, people with disabilities, and casual players